Paleoethnobotanical contributions to 18th century Inuit economy: an example from Uivak, Labrador - Zutter, Cynthia (My University, 2009)
Only a small number of archaeological research projects have investigated the interaction between the Inuit and their use of plants as part of their economy. The research presented here provides a robust illustration of the potential that archaeobotanical analysis can bring to arctic archaeology. As part of a larger multidisciplinary archaeological investigation at Uivak 1 site (HjCl-11), northern Labrador, archaeobotanical samples were recovered from multiple of contexts within the site. Results suggest that a variety of plant taxa in significant quantities were recovered from all contexts of the site. Of note are the ubiquitous berry seeds recovered throughout site, suggesting that berries were an important aspect of 18th century Inuit life-ways.
Keywords: archaeobotany; Inuit; Labrador